STRUKTUR DAN KOMPOSISI VEGETASI MANGROVE DI DESA PONDING-PONDING KECAMATAN TINANGKUNG UTARA KABUPATEN BANGGAI KEPULAUAN - Farda Almaidah; Ramadhanil Ramadhanil; Samsurizal M. Suleman (Biocelebes, 2015)
This research was carried out in Ponding-ponding village, on June and July 2014. The aim of the research is to identify structure, composition and environment condition of mangrove vegetation in Ponding-ponding Village District North Tinangkung Banggai Islands Regency. Research method used was belt transect method with position in nested plot, location of the study consisted of 3 stations are placed purposive sampling, data was analyzed using vegetation analysis. The results showed that the true mangrove species found in the village of Ponding-ponding are 6 type of Avicennia officinalis, Schyphiphora hydrophyllacea, Lumnitzera racemosa, Lumnitzera littorea, Rhizophora mucronata and Nypa fruticans. At station I, the highest IVI in the tree stratum, sapling and seedling is Avicennia officinalis with importance value each of it (257.52 %), (220.24 %) and (88.89 %). At station II, the highest IVI in the tree stratum is Schyphiphora hydrophyllacea (181.54 %), sapling and seedling stratum is Lumnitzera racemosa each of it have importance value (117.67 %) and (56.17 %). At station II, the highest IVI in the tree stratum, sapling and seedling is Nypa fruticans with details amount sapling (227,93 %) and seedling (200 %).Key words: Structure, Composition, Mangrove Vegetation, Ponding-ponding village